A conceptual model for business and information technology stratetegic alignment from the perspective of small and medium enterprises - Alyahya, Majed; Suhaimi, Mohd Adam (Centre for Promoting Ideas, USA, 2013)
Small and Medium Enterprises (SMEs) play a significant role in the economy, especially in poverty relief, job creation, and economic growth. To effectively improve the competitiveness and performance of SMEs, the adoption of Information Technology (IT) should be aligned with their business objectives. Despite the importance of the IT-business strategic alignment, past researches are concentrated on large organizations in the developed nations. Up to date, there is dearth of researches undertaken on SMEs, particularly in developing nations. Though voluminous strategic alignment models are available for large organizations, the inherent differences between SMEs and large organizations make these models irrelevant to SMEs. Thus, this study aims to propose a conceptual IT-business strategic alignment model for SMEs operating in Saudi Arabia. The proposed model is expected to serve as the stepping stone for the future researches to design more effective strategic alignment approaches for SMEs.